Clinical application of hysteroscopic hydrotubation for unexplained infertility in the mare. (5th December 2017) - Inoue, Y.; Sekiguchi, M.
Summary: Background: Therapeutic techniques for oviductal obstruction in the mare are limited. Nonsurgical and retrograde flushing may be an attractive alternative to current treatment methods for oviductal blockage. Objectives: To evaluate hysteroscopic selective hydrotubation as a treatment option for presumptive equine oviductal blockage. Study design: Retrospective case series. Methods: A quantity of 10 mL of saline was flushed through the oviducts in 28 standing sedated mares, which had reproductive histories of unexplained subfertility, by inserting a catheter into the uterotubal junction under endoscopic guidance. All mares in the study had been mated through several cycles (2–20 oestrous cycles) by known fertile stallions prior to treatment, with no evidence of conception. The average number of cycles for each mare prior to treatment was 6.5 ± 4.5. Results: Saline was successfully infused into a total of 50 oviducts. Of 28 mares, 26 conceived after the treatment. The average number of cycles for each mare to become pregnant after treatment was 1.8 ± 0.8. Main limitations: Diagnosis of blocked oviducts was presumptive, and pretreatment infertility was used as the control. Conclusions: This study revealed that hysteroscopic hydrotubation using saline improved pregnancy rates in mares in which oviductal blockage was suspected as a cause of unexplained subfertility.